(untitled) (Research, Society and Development, 2024)
The aim of this study was to investigate the influence of increasing the distance between the radiographic tube focus and the detector (known as Focal-Detector Distance (FDD)) on image quality (IQ) and radiation dose applied to the patient during pelvic radiographic examinations. For this purpose, we employed a radiographic system, a semi-anatomical model of the pelvis, and a computerized radiology system (CR) for image acquisition and digitization. We varied the FDD according to the inverse square law and maintained the exposure index (IE) with five different voltage values. We measured Incident air kerma (INAK) with a dosimetric set and analyzed IQ using public software for histogram and regions of interest (ROI). We evaluated the signal-to-noise ratio (SNR) and the radiographic contrast (CR) as IQ descriptors. Comparing the images obtained with the standard 1-meter technique, we found that increasing the FDD by 50% (from 1.0 to 1.5 m) and the voltage by 24.68% (from 77 to 96 kVp) resulted in a significant 43.1% reduction in INAK, with no significant alteration in SNR, and the IE remained within the limits established by the manufacturer. Additionally, there was a minimal 0.2% reduction in CR (from 43.0 to 42.0). Our results indicate that using an FDD larger than the standard for pelvic examinations offers a highly favorable cost-benefit ratio.